2015
DOI: 10.1093/cercor/bhv111
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of Social Perception and Cognition in the Superior Temporal Sulcus

Abstract: The superior temporal sulcus (STS) is considered a hub for social perception and cognition, including the perception of faces and human motion, as well as understanding others' actions, mental states, and language. However, the functional organization of the STS remains debated: Is this broad region composed of multiple functionally distinct modules, each specialized for a different process, or are STS subregions multifunctional, contributing to multiple processes? Is the STS spatially organized, and if so, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
341
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 375 publications
(377 citation statements)
references
References 71 publications
33
341
1
2
Order By: Relevance
“…The pSTS face region has remained an intriguing mystery ever since it was shown to respond threefold more strongly to dynamic faces than to static faces (34), and to respond equally to videos of faces and recordings of voices (31,33,39). Here we found that this region also shows some sensitivity to both the presence and nature of social interactions depicted with point-light displays and animated shapes, implicating this region in the perception of third-party social interactions.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…The pSTS face region has remained an intriguing mystery ever since it was shown to respond threefold more strongly to dynamic faces than to static faces (34), and to respond equally to videos of faces and recordings of voices (31,33,39). Here we found that this region also shows some sensitivity to both the presence and nature of social interactions depicted with point-light displays and animated shapes, implicating this region in the perception of third-party social interactions.…”
Section: Discussionmentioning
confidence: 48%
“…Relationship to nearby ROIs. We next asked how the SI-fROI compares in location and response profile to established nearby regions engaged in other social tasks, namely the right temporal parietal junction (TPJ) (29,30) and the right pSTS "face" region [referred to as such because that is the contrast by which it is defined, even though this region is now known to respond similarly to voices (31)(32)(33)]. To define these fROIs, we ran standard face (34) and theory of mind (35) localizers and used a similar group-constrained subject-specific method as described above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the STS and TPJ have long been understood to play central roles in ToM, and in particular, developing a working understanding of other people's intentions [61,63]. The STS is a central neural hub for social cognition processing, key for understanding other's actions and intentions, as well as perceiving human faces and motion [64].…”
Section: Neural Network Tom and Bpdmentioning
confidence: 99%
“…A fuller description of how the brain represents mental states would need to trace the flow of information from social perception [seeing people behave in certain ways, known to be represented in specific regions of association cortex (8)] to what is presumably a series of neural representations that comprise the transformation from perception to the inference of mental states. The representations revealed in the present study are explicit representations that correspond to how we talk and think about mental states.…”
mentioning
confidence: 99%